Textural Analysis of Nuclear Mitotic Apparatus Antigen (NuMA) Spatial Distribution in Interphase Nuclei from Human Drug-Resistant CEM Lymphoblasts - Naima Rafki‐Beljebbar; Françoise Liautaud‐Roger; Dominique Ploton; Jean Dufer (Analytical Cellular Pathology)
In tumour cell lines, the resistance of cancer cells to a variety of structurally unrelated chemotherapeutic drugs is termed multidrug‐resistance or MDR. We reported previously that MDR leukemic cells displayed nuclear texture changes, as assessed by image cytometry. The nature of these changes remained uncertain but they could be associated with alterations of the nuclear matrix which could serve an important role in DNA organization and chromatin structure. Therefore, we have compared the textural features observed in G0/G1 nuclei from human leukemic CEM cells and their MDR variant CEM‐VLB, after staining of either DNA by Feulgen method or nuclear matrix by immunodetection of NuMA antigen on DNase treated samples. Chromatin or NuMA distributions within the nucleus were evaluated by image cytometry. Changes in textural parameters indicate that modifications of NuMA distribution observed in MDR cells are parallel to those observed at the whole chromatin level (i.e., a more decondensed and coarse texture with increase of Energy and Long‐run sections and decrease of Contrast and Short‐run sections). Moreover, Optical Densities measurements indicate that MDR cells seem to contain less NuMA, a datum confirmed by immunoblotting of nuclear proteins. In conclusion, chromatin changes observed by image cytometry in drug‐resistant human leukemic CEM cells appear associated with modifications of the nuclear matrix structure.